Psychometric properties of the Arabic version of the International Consultation on Incontinence Questionnaire on Long‐Term Catheter Quality of Life. Issue 3 (18th December 2019) - Youssef, Naglaa; Best, Catherine; Mackay, William Gordon; Hagen, Suzanne; Shepherd, Ashley
Abstract: Aim: To translate the International Consultation on Incontinence Questionnaire (ICIQ) Long‐Term Catheter Quality of Life (LTCqol) questionnaire (ICIQ‐LTCqol) from English to Arabic and evaluate its psychometric properties. Background: Currently, no tool for Arabic‐speaking patients is available to measure the quality of life in patients using long‐term urinary catheters. Design: Translation and psychometric assessment of questionnaire. Methods: The internal consistency and construct validity of the translated Arabic version of the ICIQ‐LTCqol were evaluated in a convenience sample of 141 participants recruited from a hospital in Egypt from April to September 2017. Test‐retest reliability was assessed for a sample of 15 participants who completed this version at two time points. Construct validity was assessed by factor analysis. Results: The translated Arabic version of the ICIQ‐LTCqol showed satisfactory test‐retest reliability and internal consistency, with the Cronbach α = .75. Confirmatory factor analysis confirmed the same two factors ("catheter function" and "lifestyle") structure as found in the English version of the tool supporting the construct validity of the translated questionnaire. Conclusion: This original and significant study allows, for the first time, researchers and clinicians working with Arabic‐speaking patients, the opportunity to evaluate the quality of life in long‐term urinary catheter users. SUMMARY STATEMENT: What is known about this topic: The potential negative impact of using a long‐term indwelling urinary catheter on patients' everyday lives has been well documented. There is no available psychometrically robust self‐report questionnaire that can be used to assess the impact of living with a long‐term catheter among Arabic speakers. To date, the Incontinence Questionnaire (ICIQ) Long‐Term Catheter Quality of Life (LTCqol) questionnaire (ICIQ‐LTCqol) has not been translated into Arabic, and therefore, it has not been used with Arabic‐speaking catheter patients. In Arabic countries, no research has been conducted focusing on the experience of patients with urinary catheters. What this paper adds? The International Consultation on Incontinence Questionnaire (ICIQ) Long‐Term Catheter Quality of Life questionnaire (ICIQ‐LTCqol) Arabic version is a clear, understandable, and short questionnaire. The Arabic version of the ICIQ‐LTCqol has the same factor structure as the English version using confirmatory factor analysis. The Arabic version of the ICIQ‐LTCqol has good internal consistency. Implications of this paper: Clinicians and researchers working with Arabic‐speaking patients, who use long‐term urinary catheters, can utilize this version of the ICIQ‐LTCqol to evaluate their QOL. The Arabic version of the ICIQ‐LTCqol is a robust tool for assessing the impact of living with a long‐term catheter in Arabic countries. Further research is needed on the retest reliability of the ICIQ‐LTCqol in the Arabic‐speaking population. The impact of living with a long‐term catheter has not been investigated in Arabic countries.